2013
DOI: 10.19173/irrodl.v14i1.1351
|View full text |Cite
|
Sign up to set email alerts
|

Identifying barriers to the remix of translated open educational resources

Abstract: Remix is touted as one of the most important practices within the field of open educational resources (OER). But remixing is still not mainstream practice in education and the barriers and limitations to remix are not well known. In this article we discuss the design and development of a print and web-based booklet created to introduce the topic of OER to schoolteachers. The guide, the first of its kind available in Portuguese, was created through the remix and translation of existing resources available in En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 17 publications
0
16
1
4
Order By: Relevance
“…In other words, these demographic factors neither restricted nor facilitate the use of self‐directed learning strategies. This finding is contrary to some previous research claiming that non‐formal learners’ demographic factors, such as level of highest educational attainment (eg, Gillani & Eynon, ) and first language (eg, Amiel, ), are related to their participation. However, Kizilcec et al () did not report any differences between genders regarding engagement in OER‐based learning.…”
Section: Discussioncontrasting
confidence: 99%
“…In other words, these demographic factors neither restricted nor facilitate the use of self‐directed learning strategies. This finding is contrary to some previous research claiming that non‐formal learners’ demographic factors, such as level of highest educational attainment (eg, Gillani & Eynon, ) and first language (eg, Amiel, ), are related to their participation. However, Kizilcec et al () did not report any differences between genders regarding engagement in OER‐based learning.…”
Section: Discussioncontrasting
confidence: 99%
“…This is an issue of equity, which is not just of concern to open and distance educators, but has been a mainstay in other areas, such as multicultural education (Sleeter & Grant, 1994). The one-way flow of English-language content to other groups takes novel forms, such as that of translated or subtitled content (Amiel, 2013;Ochoa, Klerkx, Vandeputte, & Duval, 2011). Examples of this phenomenon include the large-scale translation of content from projects such as Coursera (in Mexico) and Khan Academy (in Brazil) ii .…”
mentioning
confidence: 99%
“…The study by Rolfe (2012) also revealed staff requirements for technical assistance and clarity over copyright. The issues of attribution, authorship, and ownership are complex tasks, especially while remixing and reusing content, and the issues of language and context make the straightforward reuse of resources difficult (Amiel, 2013). The findings of the present study suggest that a large number of respondents (95.6%) desired proper attribution to the resources made available.…”
Section: Discussionmentioning
confidence: 67%